SPINAL-INDUCED HYPOTENSION REDUCTION WITH ONDANSETRON IN CESAREAN SECTION PARTURIENTS. - Mohanty, Ranjita (Student’s Journal of Health Research Africa, 2023)
Background: During surgery in the lower part of the body especially during c-sections done by obstetricians, the favourable way of anesthetizing patients is by giving spinal anesthesia also called subarachnoid block. However, during subarachnoid block, hypotension and bradycardia may occur which has adverse effects on the fetus as well as the mother. The Bezold Jarisch pathway induced by serotonin after the anaesthesia causes the above events. Serotonin acts on 5-HT3 receptors located in the vagal nerve ending of the heart. Ondansetron blocks the activity of serotonin in its receptors. Aim: This study assesses the effectiveness of ondansetron in blocking the serotonin receptors to prevent hypotension and bradycardia in parturients having c-section surgery which requires subarachnoid block. Method: 72 women undergoing parturition by c-section were selected for the study. They were divided into two groups randomly. O group consisted of 36 women who were given 4.5mg (2.25 ml) of ondansetron intravenously before spinal anesthesia. S group women also consisted of 36 women who were given 2.25ml of normal saline before spinal anaesthesia. 2ml of 0.5% hyperbaric bupivacaine was injected intrathecally. Both groups were closely monitored for their heart rate, blood pressure, and requirements of vasopressor agents. Results: The reduction of the average pressure in the arteries was lower than 35 minutes in the group that received ondansetron. The incidence of emesis and nausea was lesser among these patients when compared to the other group. The other group had a reduction of mean arterial pressure around 14 min. Conclusion: The requirement for vasopressors decreased among the women having c-sections who had been given Ondansetron 4.5 mg intravenously before anaesthesia. Recommendation: Ondansetron may be recommended as a prophylaxis for hypotension and bradycardia following spinal anaesthesia; the level of evidence was moderate with a high level of heterogeneity.